2022
DOI: 10.3389/fbioe.2022.859255
|View full text |Cite
|
Sign up to set email alerts
|

An in Silico Approach to Reveal the Nanodisc Formulation of Doxorubicin

Abstract: Molecular dynamic behaviors of nanodisc (ND) formulations of free doxorubicin (DOX) and DOX conjugated lipid prodrug molecules were investigated by molecular dynamics (MD) simulations. We have unveiled how formulation design affects the drug release profile and conformational stability of ND assemblies. Our simulation results indicate that free DOX molecules loaded in the ND system experienced rapid dissociation due to the unfavorable orientation of DOX attached to the lipid surface. It is found that DOX tends… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 31 publications
0
9
0
Order By: Relevance
“…We focused on this kind of functionalization because of the chemical affinity between the CO group of PHBH and the −CO−CH 3 group of acetylated CNC, where strong dipole−dipole interactions are expected to be established. 42 Furthermore, we favored this particular acetylation procedure because it is a greener chemical route for grafting acetyl groups on the CNC surface, as compared to the majority of processes that employ organic solvent, like dimethylformamide (DMF) or pyridine, which have been extensively used in previous research, 40,43 and whose ecological impact is certainly negative. A clear indication that the functionalization occurred positively was given by the results of FT-IR characterization (Figure 2a).…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…We focused on this kind of functionalization because of the chemical affinity between the CO group of PHBH and the −CO−CH 3 group of acetylated CNC, where strong dipole−dipole interactions are expected to be established. 42 Furthermore, we favored this particular acetylation procedure because it is a greener chemical route for grafting acetyl groups on the CNC surface, as compared to the majority of processes that employ organic solvent, like dimethylformamide (DMF) or pyridine, which have been extensively used in previous research, 40,43 and whose ecological impact is certainly negative. A clear indication that the functionalization occurred positively was given by the results of FT-IR characterization (Figure 2a).…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…Preparation of Empty Nanodiscs and GSK-J4-Loaded Nanodiscs (ND-GSK-J4). 26,41,42 The ability of ND to target macrophages was accomplished by DPPS, 43 and the ND assemblies were prepared according to a previously reported method with some modifications. 28 Briefly, 1,2-dipalmitoyl-sn-glycerol-3-phosphocholine (DPPC) and 1,2dipalmitoyl-sn-glycero-3-phospho-L-serine (DPPS) were dissolved in chloroform in a glass tube at a 9:1 molar ratio.…”
Section: Author Informationmentioning
confidence: 99%
“…In addition, cell-level experiments revealed that KDM6B promoted the differentiation of BMDM into M2. Endogenous and synthetic lipoproteins, such as high-density lipoprotein (HDL) nanodiscs, have emerged as a promising drug delivery system (DDS) for small molecules, peptides, and nucleic acids due to their inherent long half-life in vivo and passive targeting characteristics. , Based on our recently reported work on reprogrammable peptide analogs of apolipoprotein A-I (APA) for tunable nanodisc engineering, we propose a GSK-J4-loaded nanodisc (ND-GSK-J4) targeting macrophages in bone by introducing a bone formation surface-targeting peptide-modified membrane scaffold (SDSSD-APA) and administered it to mice. After administration, it was noted that macrophages in the bone marrow of mice tended to exhibit the M1 type, and bone loss increased.…”
Section: Introductionmentioning
confidence: 99%
“…In another study, we developed an osteoblast-targeting peptide fused with APA, which can assemble into NDs and is loaded with a lysine-specific demethylase 6B (KDM6B) inhibitor for bone and macrophage dual-targeted delivery, and explored the role of KDM6B in osteogenic differentiation of mesenchymal stem cells (MSCs) and its interaction with macrophages [ 33 ]. Recently, we explored the ND formulation of Doxorubicin (DOX), a potent cancer drug, using molecular dynamics (MD) simulations [ 34 ]. Our study revealed differences in drug release profiles and conformational stability between free DOX and lipid-conjugated DOX-prodrug ND formulations.…”
Section: Introductionmentioning
confidence: 99%